Relevancia jurídica de la infidelidad virtual como causal de separación de cuerpos y divorcio ulterior en Perú, 2021-2022 - Pezo Flores, Karen Jessy (2023)
The development of information technology in recent decades has created a feasible environment for virtual infidelity, a situation in which a spouse can maintain communication and share personal information of sexual connotation with a third party, this being a serious enough fact that it could generate the affectation in the harmony of the marital relationship. Thus, virtual infidelity has currently acquired an important social relevance that entails the need for its prompt insertion within our legal system as grounds for dissolution of marriage. In this line, the main objective of the investigation was to analyze the factual and legal relevance of virtual infidelity in the framework of the grounds for separation of bodies and divorce in Peru. The research was of a basic type of descriptive level, using a functional legal-dogmatic and sociological research model, under a non-experimental methodological design, with a qualitative approach. The following results were obtained: i) Virtual infidelity has factual relevance insofar as it generates a social and personal impact that can destroy well-being within the marriage, ii) By virtue of tis factual relevance, virtual infidelity must be included in the Peruvian Civil Code together with physical infidelity to establish a more complete causal, iii) Virtual infidelity is an autonomous concept and different from that of adultery, since the existence of intercourse is not required; Likewise, it differs from serious injury, because it is a more specific conduct, since it seeks the protection of the duty of fidelity, not to honor.